3D Printed Posterior Connector Dimensions’ Effect on Fracture Properties of Provisional Two-Unit Fixed Dental Prostheses - Turki S. Alkhallagi; Manal A. Alqahtani; Thamer Y. Marghalani (Applied Sciences, 2025)
This in vitro study aims to investigate the fracture properties of 3D-printed resin provisional material designed with different connector dimensions for two-unit fixed dental prostheses (FDPs). The master model was digitally designed following Shillingburg’s all-ceramic restoration tooth preparation guidelines and milled from aluminum. Four two-unit FDPs with different connector dimensions were designed: 2 × 3 mm, 3 × 3 mm, 3 × 4 mm, and 4 × 4 mm (width × length) (Groups A, B, C, and D, respectively; n = 10 for each group). These specimens were printed using 3D-printed resin material (Detax FREEPRINT® temp). Forty specimens were subjected to a three-point test using a universal testing machine until fracture. The failure mode was examined under a stereomicroscope. The Kruskal–Wallis test at α = 0.05 revealed non-significant differences in fracture resistance load but significantly different elastic modulus, yield strength, and compressive strength (p = 0.061, p < 0.001, p < 0.001, and p < 0.001, respectively) among the different groups. The 2 × 3 mm connectors had higher means of modulus, yield strength, and compressive strength compared to the other groups. The study found that the maximum load causing fractures in 3D-printed provisional material connectors was consistent, regardless of connector cross-section variations. The 2 × 3 mm group performed best, while the 4 × 4 mm group performed worst.